Primary Non-Hodgkins lymphoma of the parotid gland - Dispenza,Francesco (2011)
Primary malignant lymphomas in the salivary glands are relatively rare. Clinical presentation is not characteristic and the disease is often overlooked resulting in diagnosis and treatment delays. AIM: To stress the importance of the diagnostic process and combined management, we present a series of eight patients with malignant lymphoma of the parotid who were diagnosed only after surgery and managed with radiation and chemotherapy. METHODS: Retrospective series of patients with primary malignant lymphoma of the parotid gland managed with radiotherapy and diagnostic surgical partial resection. RESULTS: After treatment completion we achieved a loco-regional control rate of 87.5%. Toxicity was charted according to the Common Toxicity Criteria and it was seen in six patients (75%). Six patients are still alive without evidence of recurrent disease in their last follow-up. CONCLUSION: Our study confirms that primary early stage Non-Hodgkin Lymphoma of the parotid gland is a disease with an excellent prognosis and a good local control rate, with minimal morbidity.